Molecular Detection of OXA-143 beta-lactamase gene in P. aeruginosa: Deteksi molekuler gen beta-laktamase OXA-143 pada P. aeruginosa - Abed, Jasim Mohammed; Al-Khamis, Ahmed Ramadan Hadabi; Sameer, Hamid Kadhim; Hassun, Ahmed Faleh (Indonesian Journal on Health Science and Medicine, 2025)
Pseudomonas aeruginosa, an opportunistic-bacteria that causes many clinical and hospital infections, struggles to be treated due to its drug resistance. This bacterium resists beta-lactams by producing broad-spectrum beta-lactamases. This study will determine antibiotic resistance and identify the blaOXA-143 gene in clinical P. aeruginosa isolates. This study isolated P. aeruginosa from patients using McConkey agar. Gram staining, oxidase, catalase, MRVP, motility in SIM medium, and fluorescent pigment synthesis on cetrimide agar identified and validated P. aeruginosa isolates. DNA was extracted from isolates using the kit. Primers were created and confirmed using NCBI. PCR was used to detect blaOXA-143. The 16S rRNA gene was PCR-analyzed to confirm the isolates and test the PCR test. P. aeruginosa was isolated from 100 samples: blood (36%), urine (30%), wound (20%), and trachea (14%). Penicillin had 100% resistance in a study of 100 P. aeruginosa isolates, followed by cefixime at 86%. Ipenem, meropenem, calcitin, and cefotaxime had resistance rates of 42%, 40%, 68%, and 50%, respectively. The lowest Cefepim resistance was 34%. In this investigation, 47% of isolates were multidrug-resistant. All isolates were verified by 16SrRNA detection. None of the isolates had the blaOXA-143 gene. Highlights: aeruginosa shows high resistance to multiple antibiotics. 47% isolates were multidrug-resistant, confirmed via 16S rRNA. blaOXA-143 gene was not detected in any isolates. Keywords: P. aeruginosa, beta lactamase, Oxacillinase, blaOXA143